Survey of bee fauna and conservation status indicators in a restored Atlantic Forest fragment in Araras, São Paulo - Fernandes Giroto, Marília; Carolina Montagnana, Paula; Cornélio Ferreira Nocelli, Roberta; Bürger Patrício-Roberto, Gleiciani; Roberto, Matheus Mantuanelli (Revista Ensaios Pioneiros, 2025)
The Atlantic Forest is recognized for its high biodiversity and endemism. In Brazil, it has faced severe deforestation, with considerable reduction in its original area and loss of biodiversity; thus it is crucial to prioritize it for restoration and preservation efforts. Given that bees are essential in maintaining plant diversity and that landscape alterations are a major factor responsible for the pollinator’s decline, this study aimed to identify the bee fauna of an Atlantic Forest restored fragment. Bees were collected monthly using pan traps and aromatic traps over 12 month. In total, 208 individuals from the Apidae and Halictidae families were collected. Eulaema nigrita, the most abundant species (40.86%), was exclusively captured in aromatic traps, whereas Melitoma segmentaria (9.61%), predominantly collected in blue pan traps, was the second most abundant species. The species accumulation curve showed that 12 months of sampling period was insufficient to catalog the entire bee community, with an estimated additional 13 months required to reach sample stability. Although the complete bee community was not recorded, the major abundance of E. nigrita and M. segmentaria, both recognized as a bioindicator of disturbed fragments, indicates that the forest fragment is not in an optimal conservation condition, requiring additional studies to evaluate the real conservation status. Regardless of this, our results underscore the importance of monitoring the ecological health of this restoration fragment, which could provide essential data to inform future research focused on developing management and conservation strategies for pollinators and native or restored forests.